2017
DOI: 10.1044/2017_jslhr-s-15-0438
|View full text |Cite
|
Sign up to set email alerts
|

Range and Precision of Formant Movement in Pediatric Dysarthria

Abstract: Purpose: This study aimed to improve understanding of speech characteristics associated with dysarthria in children with cerebral palsy by analyzing segmental and global formant measures in single-word and sentence contexts. Method: Ten 5-year-old children with cerebral palsy and dysarthria and 10 age-matched, typically developing children participated in this study. Vowel space area and second formant interquartile range were measured from children's elicited productions of single words and sentences. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…A study (28) found smaller vowel spaces in children with cerebral palsy compared to children with typical development in both the word and phrase contexts. However, variations of the second formant did not differ between groups for word or phrase contexts, but presented smaller values in simple words, with phonetic contexts requiring large changes in vocal tract configuration.…”
Section: Discussionmentioning
confidence: 95%
“…A study (28) found smaller vowel spaces in children with cerebral palsy compared to children with typical development in both the word and phrase contexts. However, variations of the second formant did not differ between groups for word or phrase contexts, but presented smaller values in simple words, with phonetic contexts requiring large changes in vocal tract configuration.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, from a developmental perspective, speech sounds requiring jaw movements are acquired earliest due to their reduced complexity and reduced degrees of freedom of movement (Green et al 2000). It should be noted that results of Allison et al (2017) bring evidence against the notion of consistently reduced range of articulatory targets among children with CP. Instead, the authors indicate that impaired acoustic measures may be attributed to imprecision and impaired coordination of speech movements.…”
Section: Vfdmentioning
confidence: 99%
“…These utterance-level intelligibility scores were averaged across utterances of the same length to obtain an intelligibility score for single words and sentences of each length for each listener (e.g., intelligibility scores of all two-word sentences from the TOCS+ were averaged to obtain a mean two-word intelligibility score). For each child, overall intelligibility was determined by averaging the single word and sentence intelligibility scores for each listener and then calculating the mean overall intelligibility scores across the five listeners, consistent with procedures used in prior publications (Allison, Annear, Policicchio, & Hustad, 2017;Allison & Hustad, 2018;Hustad et al, 2010;Hustad, Oakes, McFadd, & Allison, 2016).…”
Section: Childmentioning
confidence: 99%